Research progress on mechanisms of tumor immune microenvironment and gastrointestinal resistance to immunotherapy: mini review - Zhang, Zheng; Wu, Yangping (Frontiers in Immunology, 2025)
Gastrointestinal (GI) tumors present a major clinical challenge due to complex immune evasion mechanisms and generally poor responses to immunotherapy. Tumor immune microenvironment (TIME) is a critical determinant of immunotherapy resistance. Immunosuppressive cell populations such as regulatory T cells, M2-polarized tumor-associated macrophages, and cancer-associated fibroblasts, together with aberrant cytokine networks and mechanical stress in the tumor stroma, cooperate to exclude T-cell infiltration and induce T-cell exhaustion, thereby undermining the efficacy of immune checkpoint inhibitors. In addition, TIME-driven signaling pathway activation and epigenetic reprogramming further reinforce immune escape and therapeutic failure. Recent advances in single-cell and spatial transcriptomic technologies have greatly improved our understanding of these processes. Meanwhile, strategies including multi-target combination immunotherapies, epigenetic modulators, mRNA vaccines, and gut microbiota interventions are under active investigation to reverse resistance and remodel the TIME. This mini review summarizes the multifaceted mechanisms of immunotherapy resistance in GI tumors and discusses the potential of emerging therapeutic strategies to improve clinical outcomes.